The Implementation Of Case Based Learning (CBL) Model To Improve Student’s Problem Solving Skills In SMP Negeri 30 Padang - Zya Zya Gusya, Cheryna; Oktavia, Rani; Yanto, Febri; Wati, Fatma (SEMESTA: Journal of Science Education and Teaching, 2025)
This study aims to examine the effect of implementing the Case-Based Learning (CBL) model on the problem-solving skills of eighth-grade students at SMP Negeri 30 Padang. The research population consisted of all eighth-grade students at the school. A quasi-experimental design with a non-equivalent control group was employed. The sample was selected using a purposive sampling technique, resulting in classes VIII B and VIII D being chosen as the experimental and control groups, respectively. The experimental class was taught using the CBL model, while the control class received instruction through a conventional learning model. Data were collected through pretest and posttest in the form of essay-type questions administered to both groups. The data were analyzed using the tʹ-test. The results indicated a significant difference in the mean scores between students taught using the CBL model and those taught using the conventional model. The tʹ-test results showed that tcount > ttable (8.544 > 2.009), leading to the acceptance of the alternative hypothesis and rejection of the null hypothesis. It can be concluded that the CBL model had a significant positive effect on the problem-solving skills of eighth-grade students at SMP Negeri 30 Padang.